Use Of Websites With Educational Content: A Study On Students Of Sports Sciences - Karakaya, Yunus Emre; Yılmaz, Metin; Şahin, Aykut (My University, 2023)
This study aims to investigate the factors that affect the use of educational websites by the students of the faculty of sports sciences in Turkey. Ethics committee approval was obtained from Fırat University (20.11.2020-24/12). To determine the factors affecting the use of educational websites of students, the “Factors Affecting the Use of Educational Websites Scale” was used. The data obtained in the study were analysed by the SPSS package software. The “One-Way Variance” analysis, which is one of the parametric tests, was conducted. Additionally, a “Pearson Correlation Analysis” was conducted to determine the level and nature of the relationships between the dependent variables. As a result of the ANOVA analysis, significant differences were observed in the variables of frequency of using educational websites and grade level. As a result of the correlation analysis, it was observed that the strongest relationship was positive and high between the scale and the \"Satisfaction\" subscale. As a result, it was revealed that educational websites were beneficial in terms of sports education. Within this framework, educational websites enabled students to share professional information among themselves, in addition to providing convenience to both students and instructors while accessing various visual materials. Furthermore, students could easily do their research via educational websites. Finally, it was determined that with the development of technology, more applications could be included in social networking environments, and they could be used more efficiently in the sports education process. In institutions that provide sports education, various trainings can be organized to raise the awareness of students about internet use in each education period.
Keywords: University; Student; Websites; Educational content; Sports education